La circulation atmosphérique dans le sud du Portugal et l'effet du réservoir d'Alqueva. Cas d’étude ALEX 2014 - Salgado, Rui (2015)
La circulation atmosphérique dans le sud du Portugal et l'effet du réservoir d'Alqueva